The effect of Tourism on the House Market: the case of Sardinia - Bianca Biagi; Alessandra Faggian (European Regional Science Association (ERSA), 2004)
This paper focuses on the effect of tourism on quality of life (QOL). Two opposite streams of thoughts exist in the related literature. On one side, tourism is seen to be a factor of development, increasing economic opportunities and therefore affecting the QOL of local residents in a positive way. On the other side, tourism is considered a factor of pressure on local areas, because it exploits natural, social and infrastructural resources therefore negatively influencing the QOL.We collected data on all the municipalities in Sardinia (the most famous Italian island as seaside resort) to try and test whether the QOL in touristic locations is positively affected by the presence of tourists. In order to measure the contribution of tourism to QOL, we applied the hedonic price method (HPM). With this methodology, the willingness to pay for QOL, i.e. its “implicit price”, is measured by the differences in property market prices. In particular, our results show that there is a clear distinction between QOL in coastal touristic locations and inland non-touristic places. This confirms our initial idea, that, under certain conditions, tourism can be seen as a positive factor rather than a negative externality. It, indeed, fosters local communities to develop appropriate amenities and facilities. In the final part of the paper, we used the results obtained in the empirical section to propose a classification of all Sardinian municipalities based on the implicit price of QOL. Key words: QOL, HPM.
Keywords: 330; QOL; HPM